Childhood Adversity and Inflammation in Breast Cancer Survivors - Crosswell, Alexandra D. (Psychosom Med, 2014)
OBJECTIVE: Elevated inflammation predicts behavioral symptoms, disease progression, and mortality in patients with breast cancer and breast cancer survivors, although predictors of inflammation remain largely unknown. Adverse experiences in childhood have been associated with higher rates of psychological and physical illness, and elevated inflammatory activity in studies of healthy adults. However, little research has examined the association between childhood adversity and inflammation in the context of cancer, where inflammation is particularly relevant for health. METHODS: The current study examined the association between three types of childhood adversity—abuse, neglect, and a chaotic home environment—and inflammatory markers (interleukin [IL]-6 and C-reactive protein), in breast cancer survivors who had completed primary cancer treatment 1 year earlier (n = 152). RESULTS: The combined measure of childhood adversity was associated with elevations in plasma levels of IL-6 (B = 0.009, p = .027, η(2) = 0.027, after controlling for age, body mass index, ethnicity, alcohol use, and cancer treatment (surgery, radiation, and/or chemotherapy). Examination of individual types of adversity demonstrated a positive association between abuse and IL-6 (B = 0.043, p = .030, η(2) = 0.026), chaotic home environment and IL-6 (B = 0.031, p = .005, η(2) = 0.043), and chaotic home environment and soluble tumor necrosis factor receptor type II (B = 0.012, p = .009, η(2) = 0.037), after controlling for relevant confounds. CONCLUSION: Childhood adversity was associated with elevated markers of inflammation in breast cancer survivors, with potential negative implications for health and well-being. In particular, chaotic home environment showed unique links with inflammatory outcomes.